A Feasibility Study on Power Generation from Solar Thermal Wind Tower: Inclusive Impact Assessment Concerning Environmental and Economic Costs - Islam Elsayed; Yoshiki Nishi (Energies, 2018)
A solar thermal wind tower (STWT) is a low-temperature power generation plant that mimics the wind cycle in nature, comprising a flat plate solar air collector and central updraft tower to produce thermal wind that drives turbines to generate electricity. The development of power generation systems toward a sustainable future needs to be made taking into account the balance between environmental impact and economic feasibility. We examine the sustainability of STWT power generation technology using the inclusive impact index light (Triple I-light), which estimates whether it is good to do the project, including both the negative environmental impact and the economic aspect. Environmental disadvantages are discussed by performing a CO2 inventory analysis for the life-cycle of the STWT power plant. Evaluation of the economic feasibility is done by calculating the levelized electricity cost (LEC), which is the cost per unit of electricity generated. From the calculations, it is found that overall system efficiency is increased by enlarging the capacity, the negative environmental impact by the STWT plant comes mainly from manufacturing stage (more than 60%), and the levelized electricity cost is dramatically decreased by enlarging the capacity of the system (about 50% reduction). A negative value of Triple I (meaning it is sustainable) can be achieved for high power generation capacity (above 100 MW). Moreover, this paper discusses the implementation and the potential of constructing offshore STWTs.